1982
DOI: 10.1159/000137742
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Interactions of Imidazolines

Abstract: Clonidine and its methylene-bridged analog, St 1913, were potent α1 and α2 adrenergic agonists in vitro. The activity of each compound at each α-receptor subtype was similar indicating that changing the nitrogen bridge of clonidine to a methylene bridge (as in St 1913) does not markedly alter the pharmacology of the compound at the receptor level. This was confirmed in vivo by the fact that the pressor effects of both compounds in pithed rats, and the depressor effects in spontaneously hypertensive rats after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…The K, values for the displacement of [3HJ-WB-4101 binding by atropine and scopolamine determined in the present study are in close agreement with values obtained by others (Cantor et al, 1983). Although rat aorta does contain both a,-and a2-adrenoceptors (Ruffolo et al, 1982), the effects of phenylephrine are almost entirely due to a stimulation of ax1-adrenoceptors (Digges & Summers, 1983). Likewise, phenylephrine has been used as the agonist of choice for a study of a1-adrenoceptormediated effects on the left atria of rats (Benfey et al, 1979).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The K, values for the displacement of [3HJ-WB-4101 binding by atropine and scopolamine determined in the present study are in close agreement with values obtained by others (Cantor et al, 1983). Although rat aorta does contain both a,-and a2-adrenoceptors (Ruffolo et al, 1982), the effects of phenylephrine are almost entirely due to a stimulation of ax1-adrenoceptors (Digges & Summers, 1983). Likewise, phenylephrine has been used as the agonist of choice for a study of a1-adrenoceptormediated effects on the left atria of rats (Benfey et al, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…We used established techniques for a quantitation of the interaction between atropine-like agents and aadrenoceptor radioligands (Abraham et al, 1981;Cantor et al, 1983) and for estimating the antagonism against phenylephrine on isolated rat aortic strips (Ruffolo et al, 1982;Digges & Summers, 1983) and left atria (Benfey et al, 1979). The K, values for the displacement of [3HJ-WB-4101 binding by atropine and scopolamine determined in the present study are in close agreement with values obtained by others (Cantor et al, 1983).…”
Section: Discussionsupporting
confidence: 87%
“…However, yohimbine did not antagonize the effects of noradrenaline either. It might be argued that the concentration of yohimbine (1 x 10-7M) was too low to exert any appreciable antagonism of noradrenaline, yet it is generally found that the threshold blocking concentration of yohimbine at presynaptic a2-adrenoceptors is 1 x 10-8 -3 x 10-8M (Ruffolo et al, 1981) and, anyway, the concentration of yohimbine used in the present experiments (1 x 10-7M) was enough to increase markedly the stimulation-evoked overflow of radioactivity. Perhaps the yohimbine-induced increase in stimulation-evoked overflow was responsible for the apparent failure of yohimbine to antagonize the effects of exogenous noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…These constants, derived from postsynaptic responses to cholinergic nerve stimulation, closely agree with our pA2 value of 7.82 obtained by measuring the [3H]-noradrenaline overflow. The pA2 values of yohimbine at postsynaptic receptor sites in aortae of species other than rat are 6.6 (guinea-pig, Grundstrom etal., 1981), 6.7 (rabbit, Furchgott, 1955) and 6.8-6.9 (cat, dog and hamster, Ruffolo, Waddell & Yaden 1982). Thus, the affinity of yohimbine for presynaptic receptors appears to be at least one log unit higher than for the classical postsynaptic oa-adrenoceptors.…”
Section: Characterization Ofpresynaptic Adrenoceptorsmentioning
confidence: 98%